Análisis del complejo orgánico REI2FOL para determinar la ruta de exposición en control del hongo (Mycosphaerella fijiensis) causantes de sigatoka negra en banano y realizar la comparación de acuerdo a su eficacia frente a dos productos del mercado. - Landín León, Jairo X. (2015)
In the laboratory of microbiology and biochemistry, Academic Unit of Chemical Sciences and Health at the Technical University of Machala, and in the laboratories of phytopathology and bioproducts the CIBE (biotechnology research center of Ecuador) ESPOL trials were implemented to investigate the sensitivity of M.